Gender Inequality in Galaksi Kinanthi Novel by Tasaro GK - Muhammad Kiki Wardana, Nailun Najah, Hidayati, (CV. Pusdikra Mitra Jaya, 2023)
The aims of this research are to identify the types of gender inequality experienced by the main character and to analyze the main character's strategies to free herself from gender inequality. This research uses formalism theory by Boris Tomashevsky and uses Simon de Beavoir’s Existentialist Feminism theory and Mansour Fakih’s Gender Inequality theory for the support theory. The methodology is applied in this research is the qualitative research method to elaborate on the phenomenon that occur. This analysis is supported by the data acquired from journals, theses, books, and novel as the data source. From this research the researcher found there are 4 gender inequality experienced by the main character that are, marginalization, subordination, stereotypes and violence. The researcher also found the main character’s strategies to free herself from gender inequality that are, women can work, women can be intellectual and women can work for the social transformation.